Liquid–Liquid Equilibria for Binary Azeotrope Mixtures of Benzene and Alcohols Using Choline Chloride-Based Deep Eutectic Solvents - Wazeer, Irfan; Hizaddin, Hanee Farzana; El Blidi, Lahssen; Ali, Emad; Hashim, Mohd Ali; Hadj-Kali, Mohamed K. (American Chemical Society, 2018)
In this study, the COSMO-RS approach was used to qualitatively and quantitatively screen five choline chloride-based deep eutectic solvents (DESs) to separate the azeotropic binary formed between benzene and either methanol or ethanol. The activity coefficient at infinite dilution was calculated to evaluate the capacity, selectivity, and performance index of each DES. The interactions between the different species were also analyzed by interpreting the σ-profile and σ-potential of each component. Then, three DESs were selected for experimental validation. They were prepared by combining choline chloride with ethylene glycol, levulinic acid, and 1,2-propanediol. The best performance in terms of distribution ratio and selectivity was achieved with choline chloride/ethylene glycol DES with 1:4 molar ratio. The experimental tie-lines were successfully correlated using the NRTL model. Regardless of the system investigated, no DES was found in the raffinate phase, implying minimal cross-contamination. Finally, 2D NMR analysis was conducted to study the extraction mechanism of alcohol and its effect on the DES structure. This analysis revealed that, when the alcohol concentration exceeds 40 mol %, the DES' hydrogen bonds are broken such that only one phase occurs and thus the separation becomes impractical.